ON LITERATURE AND ECOFEMINISM: A READING ON SARAH ORNE JEWETT'S "A WHITE HERON" - Hermes, Ernani Silverio (Revista de Estudos Acadêmicos de Letras, 2024)
Sarah Orne Jewett is an American writer of the Nineteenth Century and is associated with American Realism. One of her most known works is the short story “A white heron”, published in 1886, which is about the relation of a girl and a hunter who are in search of a white heron. Given this context, I intend, in this essay, to analyze the literary narrative through the lens of ecofeminism. This theoretical perspective tries to interwoven the oppression of women, and other oppressed groups such as children, poor people, black people, and traditional people, and the exploitation of nature. To do so, this work undertakes an analytical path considering the resizing of the fictional figure towards its relation to nature represented in the diegesis. The theoretical framework is found, mainly, in Jytte Nhanege (2011), Chen Ling (2014), and Laila Fariha Zein and Adib Rifqi Setiawan (2017). Therefore, I realize that the relation erected between character and nature points out power relations and construction of hierarchies symbolizing oppression of women and destruction of nature by men.